Qualitative and Quantitative Phase-Analysis of Undoped Titanium Dioxide and Chromium Doped Titanium Dioxide from Powder X-Ray Diffraction Data - Hari Sutrisno; Ariswan Ariswan; Dyah Purwaningsih (Universitas Gadjah Mada, 2018)
Undoped titanium dioxide (TiO2) and a series of chromium(III) doped TiO2 (Cr-doped TiOfig. 12) with various %wt Cr atom were prepared by a reflux technique. The undoped TiO2 and Cr-doped TiO2 of 1.1, 3.9, 4.4 %wt Cr atom have been successfully analyzed both qualitative and quantitative analysis of powder X-ray diffraction (XRD) data. The qualitative analysis was carried out with the identification of phases in all samples by comparison with Crystallography Open Database (COD) and International Centre for Diffraction Data (ICDD), while the quantitative phase analysis was calculated by reference intensity ratio (RIR) and whole-pattern fitting (Rietveld analysis) methods. The undoped TiO2 consist of three phases: anatase, rutile, and brookite. In the 1.1 %wt Cr-doped TiO2 are detected presenting two phases: anatase (major) and rutile (minor). In the 3.9 %wt Cr-doped TiO2 andin the 4.4 %wt Cr-doped TiO2 consist of anatase as major phase, while CrO2 and TiO2-II phases can be detected as minor phases. The undoped TiO2 was refined in the phase, crystal system and space group of anatase (tetragonal, I41/amd), rutile (tetragonal, P42/mnm) and brookite (orthorhombic, Pbca), while the 1.1 %wt Cr-doped TiO2 was refined based on anatase (tetragonal, I41/amd), rutile (tetragonal, P42/mnm). Finally, in the 3.9 %wt Cr-doped TiO2 and 4.4 %wt Cr-doped TiO2,respectively were refined in the crystal system and space group of anatase (tetragonal, I41/amd).